Totemism: A symbolic representation of a clan with specific reference to the Basotho ba Leboa – An ethnographical approach. Issue 2 (3rd July 2019) - Makgopa, Mokgale
Abstract : The aim of this article is to share some views about the social significance of totems among the Basotho ba Leboa (Northern Sotho people). As reflected in history, totems are not restricted to any particular continent, but are found throughout the world, including Africa, the Arctic polar region, Australia, Eastern Europe and Western Europe. To achieve the goal of this article, it will be shown how totemism reflects a connection between animals and human beings regarding power, wisdom, spirits, respect, trust and understanding. In totemistic beliefs, symbolic representation plays a significant role as the human being seeks to imitate the animal totem's traits. This shall be demonstrated by demystifying the classification of various animal totems, categorising them into clans or groups, and evaluating their distinct features or characteristics and their impact on the human being. The fact that totems in the Northern Sotho culture are slowly dying out could perhaps be ascribed to the negative impact that formal education has had on the indigenous knowledge systems (IKS) of the African communities in South Africa. However, IKS is currently gaining popularity and is being incorporated into the formal education system to preserve indigenous knowledge for posterity. In this study, the ethnographic approach was used to collect data.